2009
DOI: 10.1897/ieam_2008-086.1
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide risk management using indicators for vineyards in the central valley of chile

Abstract: The Apalta catchment is a wine-producing area of 1300 ha, lying south of Santiago, located in the Colchagua Valley, near Santa Cruz in the VI Region of Chile. The vineyards are planted on slopes of up to 22 degrees, the rows being aligned mainly down the slope. This cropping system and its management lead to a potential contamination of natural resources. To assess the risk of environmental contamination due to the application of pesticides in different pest control strategies, indicators at a field level were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In addition, Alister et al (2005) reported that water quantity has a significant effect on the quantity of simazine moving downward through a soil in the Mediterranean zone. Nario et al (2009), in a study on the risk of environmental contamination due to the application of pesticides in the same zone, highlighted that runoff is the main process for pesticide transport in the landscape.…”
Section: Soil Contaminationmentioning
confidence: 99%
“…In addition, Alister et al (2005) reported that water quantity has a significant effect on the quantity of simazine moving downward through a soil in the Mediterranean zone. Nario et al (2009), in a study on the risk of environmental contamination due to the application of pesticides in the same zone, highlighted that runoff is the main process for pesticide transport in the landscape.…”
Section: Soil Contaminationmentioning
confidence: 99%
“…It has been amply demonstrated that anthropogenic landscape structure influences the spatial pattern of hydro-sedimentary transfers from plots to rivers (Gascuel-Odoux et al, 2011;Levavasseur, 2012;Nario et al, 2009;Reulier et al, 2019). While the roles of land-use on soil erosion and sediment routing are well studied, the role of linear drainage infrastructure on the hydro-sedimentary dynamics at catchment scale remains complex and difficult to understand (Carluer & De Marsily, 2004;Dotterweich, 2013;Viaud et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PRIs can be used either by individuals (growers or pest managers) as a tool in the decision-making process, or by public or private agencies to guide pesticide selection. They have also been applied to assess the environmental impact of a certain pest management program over time or in different places, and to evaluate the impact of agricultural and pesticide policies (Levitan et al 1995;Gallivan et al 2001;Greitens and Day 2007) and to identify changes in environmental risk that require attention (Mouron et al 2006;Nario et al 2009). …”
Section: Introductionmentioning
confidence: 99%